Ajaran Eskatologi dalam Teks Tutur Gong Besi - Hari Harsananda; Prasanthy Devi Maheswari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Eschatology is a teaching that seems new in Hindu religious nuances, a term that is not yet popular but widely applied in society, there are various texts that describe the teachings of this eschatology, one of which is the Tutur Gong Besi text. The Tutur Gong Besi text is a text that describes this process in a comprehensive manner. details, starting from the stage of the ceremonial process, which consists of Nanem, Ngaben to Ngeroras, then the time of the ceremony which involves the calculation of Sasih and its formulation using Hindu or Wariga astrological systemics. to the qualification of the pemuput which specifically describes the competencies that a religious leader should have in presiding over the ceremony. It is hoped that a detailed description of the text will serve as a guide for the Hindu community to understand the dimensions of belief in life after death.